Insight on the Li2S electrochemical process in a composite configuration electrode. (4th February 2016) - Carbone, Lorenzo; Verrelli, Roberta; Gobet, Mallory; Peng, Jing; Devany, Matthew; Scrosati, Bruno; Greenbaum, Steve; Hassoun, Jusef
Abstract : A novel, low cost, environmentally sustainable cathode combining PEO, LiCF3 SO3 and Li2 S–C is reported for application in high-energy lithium batteries. Abstract : A novel, low cost and environmentally sustainable lithium sulfide–carbon composite cathode, suitably prepared by combining polyethylene oxide (PEO), LiCF3 SO3 and Li2 S–C powders is presented herein. The cathode is characterized in a lithium-metal cell employing a solution of LiCF3 SO3 salt in dioxolane–dimethylether (DOL:DME) as the electrolyte. The detailed NMR investigation of the diffusion properties of the electrolyte is reported in order to determine its suitability for the proposed cell. The addition of LiNO3 to the electrolyte solution allows its practical application in a lithium sulfur cell using an Li2 S–C-based cathode characterized by a specific capacity of about 500 mA h g −1 (with respect to the Li2 S mass). The cell holds its optimal performances for over 70 cycles at a C/5 rate, with a steady state efficiency approaching 99%. The X-ray diffraction patterns of the cell upon operation suggest the reversibility of the Li2 S electrochemical process, while the repeated electrochemical impedance spectroscopy (EIS) measurements indicate the suitability of the electrode–electrolyte interface in terms of low and stable cell impedance. Furthermore, the EIS study clarifies the activation process occurring at the Li2 S cathode during the first charge process, leading to a decrease of cell polarization during the following cycles. The data reported here shed light on important aspects which should be considered for the efficient application of a Li2 S cathode in lithium batteries.